Arrayed Hollow Channels in Silk‐Based Scaffolds Provide Functional Outcomes for Engineering Critically Sized Tissue Constructs. (5th December 2013) - Rnjak‐Kovacina, Jelena; Wray, Lindsay S.; Golinski, Julianne M.; Kaplan, David L.
<x xml:space="preserve">Abstract</x> In the field of regenerative medicine there is a need for scaffolds that support large, critically‐sized tissue formation. Major limitations in reaching this goal are the delivery of oxygen and nutrients throughout the bulk of the engineered tissue as well as host tissue integration and vascularization upon implantation. To address these limitations, the development of a porous scaffold platform made from biodegradable silk protein that contains an array of vascular‐like structures that extend through the bulk of the scaffold was previously reported. Here, the hollow channels play a pivotal role in enhancing cell infiltration, delivering oxygen and nutrients to the scaffold bulk, and promoting in vivo host tissue integration and vascularization. The unique features of this protein biomaterial system, including the vascular structures and tunable material properties, render this scaffold a robust and versatile tool for implementation in a variety of tissue engineering, regenerative medicine, and disease modeling applications.